Primary hyperparathyroidism - Zeynep Cetin (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2020)
Primary hyperparathyroidism (PHPT) is an endocrinological disease with parathormone (PTH) and calcium elevation. It is the most common form of hypercalcemia in the community. In this review, the definition, diagnosis, differential diagnosis and treatment of hyperparathyroidism are described.